2009
DOI: 10.1108/09555340910956621
|View full text |Cite
|
Sign up to set email alerts
|

Do many hands make light work?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 36 publications
(40 reference statements)
0
7
1
Order By: Relevance
“…Although our theorizing in this respect is closely derived from both the actually existing differences between the two types of relays and previous theorizing (Karau & Williams, 1993, 2001) and research (Hertel et al, 2008; Kerr et al, 2005; Messé et al, 2002), other factors may also be involved in the absence of motivation gains in medley relays. It may for instance be argued that this absence is due to lower group cohesion (e.g., Everett, Smith, & Williams, 1992) or lower identification with the group (see van Dick, Tissington, & Hertel, 2009, for a recent review on group identification and group motivation and performance). Although these processes may appear plausible at first sight, there are good reasons to assume that they are not the main factors in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Although our theorizing in this respect is closely derived from both the actually existing differences between the two types of relays and previous theorizing (Karau & Williams, 1993, 2001) and research (Hertel et al, 2008; Kerr et al, 2005; Messé et al, 2002), other factors may also be involved in the absence of motivation gains in medley relays. It may for instance be argued that this absence is due to lower group cohesion (e.g., Everett, Smith, & Williams, 1992) or lower identification with the group (see van Dick, Tissington, & Hertel, 2009, for a recent review on group identification and group motivation and performance). Although these processes may appear plausible at first sight, there are good reasons to assume that they are not the main factors in this research.…”
Section: Discussionmentioning
confidence: 99%
“…In the social psychological literature, this phenomenon is discussed as one of ‘social loafing’, and a ready solution has been offered to the problems it creates. In a meta‐analysis of the phenomenon, Karau and Williams (1993) reported that social loafing is eliminated when individuals work in highly valued groups (see also Van Dick, Tissington and Hertel, 2005). Likewise, Haslam (2004) argues that understanding of social loafing can be improved by enhancing the match between individuals' self‐definition and the forms of activity in which they are required to engage.…”
Section: Corporate and Organizational Identification In The Franchisimentioning
confidence: 99%
“…Failure to identify individual contributions within groups has been linked to decrease in individual effort [23] and the strategic shift of commitment towards individually assessed modules. [24] described an effect in which the most hardworking students reduce their effort in order to avoid being taken advantage of by less committed "freeloaders".…”
Section: Issues Arising From Assessment Of Individuals Within Groupsmentioning
confidence: 99%